Ethnobotanical Study of the Medicinal Plants Known by Men in Ambalabe, Madagascar - Rabearivony, Aina D.; Kuhlman, Alyse R.; Razafiariso, Zo L.; Raharimalala, Fidèle; Rakotoarivony, Fortunat; Randrianarivony, Tabita; Rakotoarivelo, Nivo; Randrianasolo, Armand; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2015)
Madagascar has high biodiversity and endemism that are threatened by growing human populations and climate change. Species loss has potential impacts on traditional knowledge and community health. The aim of this project was to identify medicinal plants known and used by men in the Commune of Ambalabe sourced from the Vohibe Forest in eastern Madagascar. Interviews were conducted that resulted in collection of 137 plant species used by men to treat illnesses, 35% of which are endemic to Madagascar. Twelve tree species were shown to have the highest Use Index among the men in Ambalabe: Noronhia gracilipes H.Perrier, Xylopia humblotiana Baill., Fenerivia ghesquiereana (Cavaco & Keraudren) R.M.K.Saunders, Phyllarthron bojeranum DC., Mauloutchia humblotii (H.Perrier) Capuron, Aphloia theiformis (Vahl) Benn., Dillenia triquetra (Rottb.) Gilg, Chrysophyllum boivinianum (Pierre) Baehni, Oncostemum boivinianum H.Perrier, Peponidium humbertianum (Cavaco) Razafim., Lantz & B.Bremer, Eugenia goviala H.Perrier, and Macaranga alnifolia Baker.